PELANGGARAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE DI PASAR MODAL (STUDI KASUS PT BANK LIPPO Tbk) - Budiartini, Dewa Ayu; Rudy, Dewa Gde; Purwanti, Ni Putu (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
One cause of the vulnerability of companies in Indonesia to economic shocks is the weakimplementation of good corporate governance. Good Corporate Governance (GCG) isbasically a concept concerning the corporate structure, division of labor, division ofauthority, sharing the burden of responsibility for each element of the corporate structure.Weak implementation of good corporate governance leads to crime and abuse in thecapital markets. Crimes and violations in the capital market is assumed to several reasons,namely blameworthiness, weakness apparatus that includes integrity and professionalismand regulatory weaknesses. Any company who is operating in the capital market shouldhave always follow the rules set by the market and the capital itself. It is necessary for thecreation of capital markets to protect the interests of investors in investment activities inthe capital market.
Keywords: good corporate governance,capital, crimes, violations